Pertanggungjawaban Pidana Pelaku Tindak Pidana Pencurian Data Elektrnoik Ditinjau Berdasarkan Undang-Undang Ite - Setya Pratama, Oktari Anggi (Universitas Jabal Ghafur, 2025)
The crime of electronic data theft or skimming is a form of cyber crime that uses information and communication technology as a tool in committing a crime with various modes so that it supports various tricks that are becoming more sophisticated day by day. The problem discussed in this research is how to prove the crime of electronic data theft/skimming in cases that occur at ATM machines? What is the criminal responsibility for perpetrators of the crime of electronic data theft/skimming in terms of the Electronic Information and Transactions Law? Normative juridical research methods. In conclusion, proof of the crime of electronic data theft or skimming occurs using evidence as regulated in Article 184 of the Criminal Procedure Code and Article 5 paragraphs (1) and (2) and Article 44 letter b of Law Number 19 of 2016 concerning Amendments to the Law. Law Number 11 of 2008 concerning Electronic Information and Transactions which is a valid means of evidence to provide legal certainty regarding the implementation of electronic systems and electronic transactions, especially in evidence and related to legal actions carried out through the system. electronically in accordance with applicable procedural law in Indonesia. Criminal liability for perpetrators of criminal acts of electronic data theft/skimming is regulated in Article 30 paragraph (2) Article 46 paragraph (2) Law Number 19 of 2016 Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. Apart from that, the crime of skimming fulfills the elements of participation as regulated in Article 55 of the Criminal Code. Keywords : Crimes of Theft, Skimming, ITE